SOME EXACT SOLUTIONS OF COUPLED NON-LINEAR HELMHOLTZ EQUATION - Inan, Ibrahim Enam (Vinca Inst Nuclear Sci, 2022)
In this study, we obtained some exact solutions of the coupled non-linear Helmholtz equation through the sub-equation method. The solutions were hyperbolic and trigonometric. We observed through MATHEMATICA 11.2 that these solutions provided the equations, and we presented graphs of some solutions in the last section.
Keywords: coupled non-linear Helmholtz equation; sub-equation method; exact solutions